Superposition solitons in two-component Bose-Einstein condensates - 王晓敏 李秋艳 李再东 (Chinese physics B, 2013)
We develop the Hirota bilinear method and obtain the exact one and two superposition soliton solutions for two- component Bose-Einstein condensates. The conversion of three kinds of solitons including the superposition solitons, bright-bright solitons, and dark-bright solitons is discussed. With the energy analysis, we find that the superposition soliton state is an excitation state for this system. Moreover, the collision of two superposition solitons is found to be elastic.